Implementasi Social Marketing pada Dinas Perindustrian dan Perdagangan Kabupaten Lamongan (Studi Kasus Local Brand Nasi Boran) - Febriana Diana Ningsih; Sukaris Sukaris (Jurnal Mahasiswa Manajemen, 2022)
Background – With the large number of Nasi Boran sellers in Lamongan City, the efforts made by researchers are to increase public awareness or love for the Local Brand of Nasi Boran in Lamongan City. Public awareness of the love of local brands is very important and needs to be considered. Therefore, researchers conducted research on how to make the public or consumers aware of the interesting for the Nasi Boran brand. Objective - This study aims to find out how to implement Social Marketing at the Department of Industry and Trade of Lamongan Regency (Case Study of Local Brand Nasi Boran). Design/methodology/approach - This study uses primary data types. This study uses qualitative techniques by taking data through interviews. Findings - The results of this study indicate that the Department of Industry and Trade of Lamongan Regency has carried out Social Marketing activities. And there are impacts in implementation which include revenue, awareness, and brand. And the love of the Lamongan community for the Local Brand of Nasi Boran can be seen through where this Nasi Boran consumer has done Social Marketing to the people around him. Research Implications – The results of this study can be used as a way to introduce Nasi Boran thoroughly to the people of Lamongan city. Research Limitations - Research barriers in getting better results in this study are at the data collection stage. The data obtained by means of interviews can be considered less representative of the variables discussed in this study.